Communication Channel Preferences: A Descriptive Audience Segmentation Evaluation - Kevan W Lamm; Abigail Borron; Jessica Holt; Alexa J Lamm (Journal of Applied Communications, 2019)
For over 70 years the use of opinion leaders in a two-step communication process has been employed and validated. However, despite the accepted importance of communicating with opinion leaders as a means to cascade information to opinion leaders’ networks of influence there have been few empirical studies specifically examining agricultural and natural resource opinion leader communication channel preferences, particularly from an audience segmentation perspective. The results reported in the study capitalize on previous research data examined from a unique perspective. Specifically, communication channel preferences were analyzed according to opinion leader self-reported demographic categories serving as audience segments. Associations between sex, age, level of employment, level of education and geographical region and communication channel preference were analyzed. The results of the study are descriptive and foundational in nature. Overall, the results indicate a dedicated web page or blog is the most preferred communication channel across all audience segments and conference calls are the least preferred communication channel across the majority of audience segments. The Facebook group communication channel had the most variability between audience segments and the LinkedIn group communicational channel had the largest observed effect sizes among audience segments.
Keywords: opinion leader; audience segmentation; communication channel preference; descriptive